Breeding resource distribution affects selection gradients on male phenotypic traits: experimental study on lifetime reproductive success in the bitterling fish (Rhodeus amarus) - Reichard, Martin; Ondracková, Markéta; Bryjová, Anna; Smith, Carl; Bryja, Josef (Evolution; international journal of organic evolution, 2009)
The spatial distribution of breeding resources can have pronounced demographic and evolutionary consequences. We used 20 experimental groups of the bitterling (Rhodeus amarus), an annual fish with a promiscuous, resource-based mating system, and extended breeding season to investigate how the spatial distribution (clumped or regular) of bitterling oviposition sites (live freshwater mussels) affected offspring production, variation in reproductive success, and directional selection on phenotypic traits over their entire reproductive lifetime. We did not detect any effect of resource distribution on offspring production or variation in reproductive success among individual fish, although variation between replicates was higher with a clumped distribution. This finding is discussed with regard to the incidence of alternative mating behaviors (sneaking) within the limitations imposed by our experimental design. Breeding resource distribution had a significant effect on selection on male phenotypic traits. Stronger directional selection on traits associated with intrasexual competition for fertilizations, gonad mass (an indicator of sperm competition), and the extent of red, carotenoid-based pigment in the iris (an index of dominance status), was detected with a clumped resource distribution. With a regular resource distribution, a stronger positive selection on male body size was detected. We discuss the implications of our results for natural populations.
Keywords: kladení vajíček; rozmnožování; ryby; Reproduction; Sexual Behavior, Animal; Fishes; Male; Animals; Female; mužské pohlaví; ženské pohlaví; sexuální chování zvířat; zvířata; Oviposition